A High‐Performance In‐Memory Photodetector Realized by Charge Storage in a van der Waals MISFET. Issue 10 (31st January 2022) - Li, Songyu; Zhang, Zeyu; Chen, Xiaoqing; Deng, Wenjie; Lu, Yue; Sui, Manling; Gong, Fan; Xu, Guoliang; Li, Xuhong; Liu, Famin; You, Congya; Chu, Feihong; et al.
Abstract: The emerging data‐intensive applications in optoelectronics are driving innovation toward the fused integration of sensing, memory, and computing to break through the restrictions of the von Neumann architecture. However, the present photodetectors with only optoelectronic conversion functions cannot satisfy the growing demands of the multifunctions required in single devices. Here, a novel route for the integration of non‐volatile memory into a photodetector is proposed, with a WSe2 /h‐BN van der Waals heterostructure on a Si/SiO2 substrate to realize in‐memory photodetection. This photodetector exhibits an ultrahigh readout photocurrent of 3.4 µA and photoresponsivity of 337.8 A W −1 in the solar‐blind wavelength region, together with an extended retention time of more than 10 years. Furthermore, the charge‐storage‐based non‐volatile mechanism of h‐BN/SiO2 is successfully proven through a novel analysis of in situ optoelectronic electron energy‐loss spectroscopy. These results represent a leap forward to future applications and insightful mechanisms of in‐memory photodetection. Abstract : An in‐memory photodetector is successfully designed based on a WSe2 /h‐BN/SiO2 van der Waals heterostructure, which demonstrates not only an ultrahigh photoresponsivity (337.8 A W −1 ) but also an extremely long‐term retention (>10 years). Moreover, the working mechanism with charge‐storage effect of the h‐BN/SiO2 structure is proved through a novel in situ optoelectronic electron energy‐loss spectroscopy analysis.